UPAYA PENYELESAIAN TERHADAP PELANGGARAN PERJANJIAN KARTU KREDIT - Shintya Purnama Dewi, Nyoman; Sukranatha, Anak Agung Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
Along with the rapid development of world trade, incuding Indonesia, the particulary demanding employers to use a practical means of payment. Especially in busy entrepreneurs who often travel abroad and require tools that are practical and flexible payments that can provide ease, smoothness and comfort of the parties involved in a transaction. Public demands are answered by the bank to issue credit card as a substitute for cash payment. But in practice often found problems related to non performance in accordance with performance agreements have been agreed. It is then in practice lead to disputes between the parties.
Keywords: Settlement Efforts, Credit Card Breach, Agreement